The effect of 1-deoxynojirimycin isolated from logging residue of Bagassa guianensis on an in vitro cancer model - Fonseca, Susanne Suely Santos da; Rodrigues, Thaíssa Vitória Portal; Pinheiro, Wandson Braamcamp de Souza; Teixeira, Eliel Barbosa; dos Santos, Kyouk Isabel Portilho; da Silva, Marcelli Geisse de Oliveira Prata; de Sousa, Amanda Marques; do Vale, Débora Monteiro Carneiro; Pinho, Jaqueline Diniz; Araújo, Taíssa Maíra Thomaz; Khayat, André Salim; Pereira, Antonio (Frontiers in Chemical Engineering, 2024)
Bagassa guianensis Aubl, a tree widely distributed in Brazil, significantly contributes to the furniture industry. Notably, it harbors the bioactive compound 1-deoxynojirimycin (1-DNJ), which is retrievable from timber residues and retains activity even days after wood extraction. This makes Bagassa guianensis a promising biological resource for anticancer therapy and pharmacology studies. This study delves into the in vitro antineoplastic actions of 1-DNJ, focusing on adenocarcinoma gastric cell lines (ACP02) and glioblastoma (A172). Assessing cell viability after 72 hours (about three days) of treatment reveals a remarkable reduction, particularly in glioblastoma cells (A172), exhibiting a lower IC50% compared to ACP02 and MRC5 (fibroblast derived from normal lung tissue) cell lines. This decreased viability correlates with reduced reactive oxygen species (ROS) production in both cell lines after the treatment with 1-DNJ. Furthermore, 1-DNJ induces cell cycle arrest, impedes cell migration, and prompts cell death in ACP02 and A172. These findings support 1-DNJ as a potent antineoplastic agent, particularly efficacious against glioblastoma and gastric adenocarcinoma. Thus, unveiling the therapeutic potential of Bagassa guianensis Aubl for cancer treatment and expanding the horizons of bioeconomy applications.